COVID-19 related information seeking: The impact of media on parental concerns - Arnaud, Yann; Drouin, Olivier; Borgès Da Silva, Roxane (Frontiers in Public Health, 2022)
The expansion of information sources and their use has accelerated since the beginning of the COVID-19 pandemic, sometimes provoking significant concern in the daily lives of parents. The objective of this study was to investigate the association between information sources and the level of concern about COVID-19 among parents of school-aged children. Using factor analysis and hierarchical ascending classification, we constructed groups according to the information sources they used. We performed ANOVA analysis and then binomial logistic regression to compare concern levels among the groups created. The 3,459 individuals in the sample fell into three groups: 1) Traditional Media (n = 1,610), who mainly used newspapers; 2) Social Networks and Entourage (n = 776), who mostly consulted social networks, friends, and family; and 3) the Unplugged (n = 1073), who consulted few or no information sources. Compared to the Unplugged, individuals in the other two groups had a higher risk of being concerned (Traditional Media, OR = 2.2; p < 0.001; Social Networks and Entourage, OR = 3.1; p < 0.001). Communication about pandemic risk should be conveyed based on reliable information and at moderate intervals to safeguard the mental health of individuals.